Assessment of Hyposalivation and Oral Health-Related Quality of Life in Patients on Polypharmacy – A Cross-Sectional Study - J Juliet Philo D Almeida; Elangovan Somasundaram; Suman J. Lakshmi; Senthilkumar Balasubramaniam (Journal of Indian Academy of Oral Medicine and Radiology)
Background: This study is centered on finding the changes in the lifestyle of individuals under polypharmacy by using specific questions about the effects of hyposalivation and collection of saliva. Aim: To evaluate the severity of hyposalivation and oral health-related quality of life in patients on polypharmacy. Objectives: To assess the effects of polypharmacy-induced hyposalivation and oral health-related quality of life according to age and gender. Materials and Methods: Stimulated salivary samples were collected in patients between the ages of 40 and 65 years, both male and female who were taking ≥2 medications daily, using the spit method. The flow was calculated based on the mL/min collecting time. Oral health-related quality of life was assessed using the “Oral Health Impact Profile-14” questionnaire. Statistical Analysis: Mean ± standard deviation (SD) of effects of polypharmacy on salivary flow rate and oral health-related quality of life according to age and gender were described, and multiple group comparisons were conducted using the ANOVA and t-test. Results: The difference between salivary flow rate and age (P = 0.564), gender (P = 0.702), duration of medication (P = 0.06), and number of drugs (P = 0.476) were statistically insignificant. Conclusion: A significance was noted according to gender based on the OHIP-14 questionnaire. There was a strong significance according to gender for the questions in the subdomain “physical disability.”